Short wave dynamics of thin plates - Ilgamov, Marat Aksanovich (Computational Continuum Mechanics, 2012)
Oscillations and waves in the plate which interacts with the gas phase are examined. It is assumed that excitation frequencies fall in the ultrasonic range, the plate thickness is small and its ratio to the half-wave length does not exceed one fifth. The simplest model developed in the paper is based on the Timoshenko plate bending theory and the first approximation for acoustic medium response. The analysis is carried out to study the dynamics of a plate of infinite and semi-infinite length and to make an order-of-magnitude estimate of input dimensionless parameters. This allows us to simplify Timoshenko equations and to get thus the observable results. The results obtained using the Timoshenko model are compared with those of the Kirchhoff model.